A Versatile Transreplication-Based System To Identify Cellular Proteins Involved in Geminivirus Replication - Morilla, Gabriel (American Society for Microbiology, 2006)
A versatile green fluorescent protein (GFP) expression cassette containing the replication origins of the monopartite begomovirus Tomato yellow leaf curl Sardinia virus (TYLCSV) is described. Transgenic Nicotiana benthamiana plants containing one copy of the cassette stably integrated into their genome were superinfected with TYLCSV, which mobilized and replicated the cassette as an episomal replicon. The expression of the reporter gene (the GFP gene) was thereby modified. Whereas GFP fluorescence was dimmed in the intercostal areas, an increase of green fluorescence in veins of all leaves placed above the inoculation site, as well as in transport tissues of roots and stems, was observed. The release of episomal trans replicons from the transgene and the increase in GFP expression were dependent on the cognate geminiviral replication-associated protein (Rep) and required interaction between Rep and the intergenic region of TYLCSV. This expression system is able to monitor the replication status of TYLCSV in plants, as induction of GFP expression is only produced in those tissues where Rep is present. To further confirm this notion, the expression of a host factor required for geminivirus replication, the proliferating cellular nuclear antigen (PCNA) was transiently silenced. Inhibition of PCNA prevented GFP induction in veins and reduced viral DNA. We propose that these plants could be widely used to easily identify host factors required for geminivirus replication by virus-induced gene silencing.